PSX-B-26 Mitotic activity of immune cells in the intestines of piglets in the treatment of gastrointestinal pathology. (8th October 2021) - Parshin, Pavel; Sashnina, Larisa; Mikhailov, Evgenii; Shabunin, Boris; Vorotnikova, Svetlana
Abstract: The study aimed to evaluate the effect of a drug based on the granulocyte-macrophage colony-stimulating factor (GM-CSF) on intestinal immune cells' mitotic activity in treating gastrointestinal pathology. Two groups of 40 sick piglets with diarrhea at the age of 5–7 days were formed. The 1st group was the control. Animals of the 2nd group received an intramuscular injection of "Quinokol"(enrofloxacin) at a dose of 0.5 ml / 10 kg once a day for 5 days. The 3d - "Quinokol" at the same dose combined with GM-CSF at a dose of 0.1 ml/kg twice with an interval of 48 hours. From forcedly slaughtered piglets (by Directive 93/119 / EC) with the diarrheal syndrome (n = 4) and from animals of the experimental groups (n = 4), duodenum sites were taken for research. Immunohistochemical study of Ki-67 expression with additional staining with hematoxylin Karratsi was carried out according to the method described by V. Stafford. Cell counting and morphometric changes were performed using the ImageJ software. In preparations from sick piglets and piglets, which were used "Quinokol", the main mitotic activity was 0.0036 ± 0.00047 and 0.0041 ± 0.00054 mitoses / μm2, respectively (fig 1 - A). Single Ki-67-positive cells were found in the stroma of the villi, vascular walls, and submucosa. In some areas, the bean or rod-shaped nucleus of Ki-67 positive cells was distinguished. At the samples from the 3d group (fig 1 - C, D), a sharp increase in the mitotic activity of immune cells in the stroma of the villi was noted - 0.0067 ± 0.00072 mitoses/μm2 and significantly more than in the 1st and 2nd groups by 64% and 86%, respectively (P < 0.001). The combined use of "Quinokol" with GMC-SF increased cell hyperplasia in the villous stroma, which indicates the activation of local intestinal immunity.